Endovascular occlusion of vertebro-vertebral arteriovenous fistula using detachable balloons: A case report - Linh Hoang Duong, MD; Giang Luu Nguyen, MD; Tran Tran Nguyen, MD; Thang Minh Le, MD; Luan Minh Bao Tran, PhD (Radiology Case Reports)
Vertebro-vertebral arteriovenous fistula (VV-AVF) is an uncommon vascular disorder characterized by an abnormal direct connection between the extracranial vertebral artery (VA), as well as the first and second branches of subclavian arteries, and the draining veins of the paravertebral venous plexus. Endovascular occlusion or surgical ligation of the high-flow arteriovenous fistula is the main goal of treatment for VV-AVF, but there are no guidelines for the best treatment to date. Endovascular treatment is the primary treatment procedure due to its safety, effectiveness, and simplicity. We reported a rare clinical case of the endovascular approach used for occlusion of VV-AVF. A 52-year-old female patient with no history of trauma was presented with right neck pain for a month. Diagnostic angiography demonstrated a high-flow VV-AVF at C3-C4 level. After endovascular occlusion with detachable-balloon embolization, the fistula was completely obliterated. To our knowledge, endovascular occlusion for VV-AVF patients is safe and effective. Detachable balloon embolization can be considered a well-tolerated treatment.